Poškodbe zadnje lože stegna - Hadžić, Vedran (Šport (Ljubljana), 2016)
Hamstring strain injuries (HSI) are the most common muscle injuries in sport. There are two main injury mechanisms: an injury during sprinting and injury due to overstretch. Numerous risk factors are known HIS such as strength ratios, fatigue and previous injury. The paper describes how to plan exercise and training following HIS in order to progressively and above all safely returns the athletes to the training/match process while eliminating known risk factors for HIS.
Keywords: biceps femoris; exercise; mišična moč; muscle strength; sport; šport; športne poškodbe; training; vadba